2016
DOI: 10.1186/s12957-016-0912-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adjuvant interferon therapy on hepatitis B virus-related hepatocellular carcinoma: a systematic review

Abstract: ObjectiveThe objective of this study is to evaluate the efficacy of adjuvant interferon therapy for hepatitis B virus-related hepatocellular carcinoma (HCC) after different previous therapy.MethodsAn electronic search for articles about adjuvant treatment with IFN for patients with HCC published between 2000 and 2015 was conducted in MEDLINE, PubMed, Cochrane Library, and EMBASE databases. All data was tested with Stata12.0 software.ResultsSix trials with a total of 1054 subjects were screened according to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Interferon has an effect on HBV DNA suppression, immunoregulation, inhibition of malignant cell proliferation and antiangiogenesis, which provide a solid theoretical basis for prevention of recurrence after HBV-related HCC resection. 38 , 44 Systematic review and meta-analysis in 2016 also confirmed that interferon-alpha adjuvant therapy significantly reduced the recurrence of HBV-related HCC surgery/interventional therapy (RR = 0.90, p = 0.02) and mortality risk (RR = 0.72, p = 0.001), as compared with the placebo control group. This benefit is more significant after hepatic arterial chemoembolization or hepatic arterial chemoembolization combined surgical treatment.…”
Section: Peg-ifn Treatment Strategy For the Population With High Riskmentioning
confidence: 85%
See 2 more Smart Citations
“…Interferon has an effect on HBV DNA suppression, immunoregulation, inhibition of malignant cell proliferation and antiangiogenesis, which provide a solid theoretical basis for prevention of recurrence after HBV-related HCC resection. 38 , 44 Systematic review and meta-analysis in 2016 also confirmed that interferon-alpha adjuvant therapy significantly reduced the recurrence of HBV-related HCC surgery/interventional therapy (RR = 0.90, p = 0.02) and mortality risk (RR = 0.72, p = 0.001), as compared with the placebo control group. This benefit is more significant after hepatic arterial chemoembolization or hepatic arterial chemoembolization combined surgical treatment.…”
Section: Peg-ifn Treatment Strategy For the Population With High Riskmentioning
confidence: 85%
“…In the natural history of CHB, the annual incidence rate of HCC in CHB patients with non liver cirrhosis ranges from 0.5% to 1%, and with cirrhosis ranges from 3% to 6%, 5 which is far higher than the general population and the incidence of liver cancer in China (0.026%). 37 Interferon has a variety of biological functions, including antiviral, antiproliferation, antiangiogenesis and immunomodulatory effects, and interferon can also achieve its antitumor effect 38 by inhibiting tumor angiogenesis and antitumor cell proliferation.…”
Section: Peg-ifn Treatment Strategy For the Population With High Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of meta-analyses indicated that IFN improved the nonrecurrence survival and overall survival following surgical resection of virus-related HCC ( 17 19 ). Moreover, IFN intervention remarkably attenuated mortality and recurrence in HBV-related patients with HCC having a therapeutic history of TACE ( 20 ). In the patient in the present case study, TACE was used comprising CDDP and FUDR for HCC, and CDDP/FUDR achieved a good tumor response ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interferon (IFN) has immunomodulatory, antiviral, antiproliferative, and antitumoral effects. Most studies have shown that IFN can delay the progression of HBV‐related liver diseases and reduce the risk of HCC recurrence, although some have shown the opposite . To assess the therapeutic value of adjuvant IFN therapy in patients with HBV‐related HCC after TACE, we carried out a randomized controlled trial in which the effects of IFN therapy on cellular immune function, HBV replication, liver fibrosis, tumor recurrence, and survival were analyzed.…”
Section: Introductionmentioning
confidence: 99%